Penggunaan Metode Analisis Tugas Untuk Pengembangan Motorik Halus Anak Tunagrahita Ringan Melalui Meronce Gelang di Slb Theresia Sonder - Rahma, Nabila; Dapa, Aldjon Nixon; Undap, Tiersa R. (Peneliti.net, 2026)
This study employed an experimental method using a Single Subject Research (SSR) approach with an A–B–A design. The subject involved in this study was a mildly intellectually disabled eleventh-grade student with the initials RS, who experienced difficulties in following instructions and coordinating finger movements during fine motor activities. Data collection techniques included observation and documentation. Data were analyzed quantitatively using graphical analysis within and across conditions. The results showed that the application of the task analysis method had a positive effect on improving the child’s fine motor skills. In the baseline-1 condition (A1), the subject’s ability was still fluctuating, with a trend stability of 20%. After the intervention was given (B), the subject’s ability increased with a trend stability of 90% and continued to improve in the baseline-2 condition (A2) with a trend stability of 80%. This was indicated by an overlap of 20%. Based on these findings, it can be concluded that the application of the task analysis method is effective in improving the fine motor skills of children with mild intellectual disabilities through bracelet-beading activities in grade XI at SLB Theresia Sonder